PENGARUH DESENTRALISASI, KETIDAKPASTIAN LINGKUNGAN, PENGENDALIAN AKUNTANSI, SERTA KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL - Bayu Sakti Wicaksono (TEMA, 2021)
This study aims to examine the influence of decentralization, environmental uncertainty, accounting control and organizational commitment to managerial performance in the Tulungagung Regency Government. Decentralization is the delegation of authority and decision-making widely to the levels below it. Environmental uncertainty is a condition felt by the government to predict something that happens in its environment. Accounting control is a control process that uses accounting data. Organizational commitment is a strong desire to become a member of an organization. Managerial Performance is a person who holds a position through an organizational unit to carry out management functions and achieve organizational goals. This type of research is hypothesis testing. The object of the study was an echelon III official within the scope of the Tulungagung Regency Regional Government. Data analysis uses multiple linear regression. The results showed that decentralization and organizational commitment affect managerial performance. Research also shows that environmental uncertainty and accounting control do not affect managerial performance.